Protegiendo las tradiciones marítimas: la prueba de los derechos de pesca tradicionales en el derecho internacional - Chagua Zúñiga, Milene Vanessa (2025)
One of the most controversial sources of public international law is customary international law, whose identification by international courts remains a significant challenge for both doctrine and jurisprudence. This difficulty arises from the absence of a clear standard for assessing the existence of a customary norm, as well as the lack of a precise and systematic methodology for determining the value of the elements that constitute it. Traditional fishing rights were part of the customary international law governing the law of the sea before the entry into force of the United Nations Convention on the Law of the Sea (UNCLOS). However, the adoption of this treaty raised questions about the legal nature of these rights and their continued recognition in the international legal framework. Proving traditional fishing rights as customary international law is a complex challenge, as it requires demonstrating both the existence of a consistent and widespread practice over time and its recognition as a legally binding obligation (opinio juris). In this context, this article will focus on analysing customary international law and its identification before the International Court of Justice, with the aim of examining how this court assesses evidence of customary international law and determining the most suitable types of proof to substantiate the customary nature of traditional fishing rights.